Variation in Eucalyptus delegatensis post-fire recovery strategies: The Tasmanian subspecies is a resprouter whereas the mainland Australian subspecies is an obligate seeder - Rodriguez-Cubillo, Dario; Prior, Lynda D.; Bowman, David M.J.S. (Forest ecology and management, 2020)
•Tasmanian subspecies of E. delegatensis recovers from fire by epicormic resprouts.•By contrast, the mainland Australian subspecies is a post-fire obligate seeder.•Tasmanian subspecies has greater resilience to fire than mainland subspecies.•Stems < 20-cm diameter of the Tasmanian subspecies are vulnerable to fire kill.•Risk of regeneration failure for several decades in clear-felled Tasmanian forests. Eucalyptus delegatensis is native to the Australian Alps (subsp. delegatensis) and montane Tasmania (subsp. tasmaniensis). Post-fire regeneration mechanisms of the obligate-seeder subspecies on the Australian mainland are well-known, but less is known about the resprouter Tasmanian subspecies. In January 2016, large tracts of Eucalyptus delegatensis forests in central Tasmania, logged at different intensities, were burnt by low- and high-severity fire. We used statistical modelling to understand how tree survival, vegetative regeneration and seedling recruitment differed according to understorey type, fire severity, logging intensity and tree size (DBH). Fire severity, defined as unburnt, low-severity (fire scarring on the stem and/or lower canopy burnt) and high-severity (full canopy burnt), affected tree survival: 84% of trees were alive in unburnt transects, compared with 43% in low-severity transects and 36% in high-severity transects. Epicormic resprouting was the dominant mode of vegetative recovery, with < 1% of total trees recovering solely by basal resprouting. Fire severity significantly affected epicormic resprouting, with 70% of live stems resprouting post-fire in low-severity transects and 99% in high-severity transects, compared with 4% in unburnt transects. Tree survival was strongly influenced by tree size: in high-severity transects, 24% of trees with DBH < 20 cm were alive, compared with 88% of trees with DBH ≥ 20 cm. These differences in survival were primarily because large trees were more likely to resprout epicormically, with epicormic shoots present on 24% of live trees with DBH < 20 cm, compared with 79% of live trees with DBH ≥ 80 cm. The strong effect of tree size renders clear-felled forests especially vulnerable to fire during the several decades when all the regenerating trees are small (DBH < 20 cm). Seedling recruitment was uncommon, independent of understorey type and logging intensity, but with higher occurrence on high-severity (54%) than low-severity (19%) or unburnt (15%) transects. When present, seedling densities were typically low: median = 400 and maximum = 4·104 seedlings ha−1. This study highlights that mature forests of Eucalyptus delegatensis in Tasmania are more resilient (able to return to pre-disturbance conditions) to single high-severity fires than their mainland counterparts, because they can recover more quickly through epicormic resprouting. However, clear-felling reduces this resilience for several decades because it decreases median tree size and, hence, leads to higher post-fire mortality. It is difficult to predict how the Tasmanian subspecies will respond to an increased frequency of high-severity fires associated with a projected warmer and drier climate.